The Role of Internal Audit Function in Supporting Good Corporate Governance Implementation in PT. Astra International, Tbk (Case Study in the Division of Sales Operation Audit) - Viranata, Kharisma K. (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study  is  aimed to understand the roles of  Internal Audit Function  (IAF), specifically Sales Operation Audit (SOA), in supporting Good Corporate Governance (GCG) implementation based on the result from external reviewers in PT. Astra International, Tbk. Case study was employed as the research method and designed to answer the research questions. The thematic and content analyses were used  for interpreting  the  data. Moreover, the data collection methods were interview, observation and documentation. The findings of this study point out three main roles of IAF, specifically SOA, in supporting GCG implementation, which reviews corporate risk, provides assurance towards corporate control and assists business activities. In reviewing corporate risk, it requires the auditor to identify and control the risk. Then, in giving assurance towards corporate control, the evaluation of internal control is conducted. The last, in assisting the business activity, auditors become the business partner for management. This study has several implications which are classified into theory, practice, and policy. The theoretical implication refers to IAF which has roles  in supporting  GCG implementation which can contribute to the development of science, particularly in the audit disciplines. In the  field of practical implication, GCG nowadays becomes the important part of company and its good performance will indicate  the business sustainability. In addition, Group Audit and Risk Advisory have the key roles which could form them as the important function in Astra. Thus, it is appropriate for them to enlarge their roles for  the achievement of company’s long-term objectives. The last is implication in terms of policy which is appropriate for regulators and standards setters to continue in encouraging the companies in Indonesia to implement the principles of GCG by creating other initiative activities and/or adding up the incentives, such as the rewards, ease of  access,  or other motivational things for the companies. Key words: Internal Audit Function, Good Corporate Governance, PT. Astra International, Tbk.